ANALISIS STRUKTUR EKONOMI DAN KOMODITI UNGGULAN DI KOTA KENDARI - Rosnawintang Rosnawintang (JEP (Jurnal Ekonomi Pembangunan), 2017)
There are three dominant economic sectors in Kendari City, namely the transportation and communication sector (24.22%), the trade, hotel and restaurant sector (19.37%), and the agricultural sector (19.26%). An interesting problem is that when economic growth is quite high simultaneously the poverty rate is also quite high. Based on the above, in Kendari City efforts should be made to reduce poverty through development policies that can encourage sustainable economic growth. One approach that can be done is through developing superior commodities in each sub-district in Kendari City. Based on this, a study of the economic structure and superior commodities was carried out in Kendari City. The study was conducted using LQ analysis, multiplier effect, AHP and simple linear regression. The results of the study show that the economy of Kendari City according to current prices has grown spectacularly in the period 2001-2005 which is equal to an average of 15.44%. In the same period (based on the constant price of 2000) economic growth was relatively more stable at an average of 8.22%. Based on LQ analysis there are five leading sectors, namely processing, electricity, gas & clean water, trade, hotel and restaurant, transportation and communication as well as finance, leasing and company services.